The brain fitness program [videorecording (DVD)] - Coyote, Peter; Brown, Eli (Santa Fe Productions, 2007)
"The Brain Fitness Progam, as seen on Public Television, is based on the concepts of neuroplasticity -- the ability of the brain to change and adapt and even rewire itself"--Container.